Development of long pulse Nd. YAG laser system - Sidi Ahmad, Muhamad Fakaruddin (2012)
The Nd:YAG laser with long pulse duration can be produced by using an appropriate pumping scheme. The purpose of this study is to construct a high voltage power supply for laser system. In this attempt multiple-mesh pulse forming technique was performed to obtain electrical pump pulses with a more rectangular shape and long normal-mode laser pulses at constant power. The flashlamp driver was designed with variable input energy. A linear xenon flashlamp was selected as an optical pump for Nd:YAG laser crystal. The developed flashlamp driver consists of five major electronic circuits. These are signal controller device, simmer power supply (SPS), trigger pulse ignition circuit, capacitor charging power supply (CCPS) and multiple-mesh LC pulse forming network (MPFN). The construction of the flashlamp driver started with the design of a signal controller. The controller generated a small voltage to activate the electronic components such as silicon controlled rectified (SCR) and transistor. The ignition circuit was used to ignite xenon gases responsible to for forming ionized spark streamer between the two electrodes of the flashlamp. A low dc current was induced by the simmer power supply to sustain the flashlamp in simmering mode. The capacitor charging power supply was used to supply electrical power to capacitor within specific time. Radiation emitted by flashlamp was used to pump the Nd:YAG crystal. As a result a powerful Nd:YAG laser beam was generated having fundamental wavelength of 1064 nm, 650 microsecond pulse duration with maximum output energy of 250 mJ.